O fazer modelagem matemática em uma atividade sobre simetria na natureza - SOUZA, Carolina Rodrigue de (2022)
This paper arose from the need to think about Mathematical Modeling as a methodological strategy in the teaching of Mathematics, developed within a student contexto that describes and delas with real problems. The work aimed to discuss the mathematical modeling of students, in initial education. This research is qaulitative, conducted with a group of 13 students, all students of the Mathematics Degree course, in the contexto of a Mathematical Modeling course developed within the Experimental Laboratory of Mathematical Modeling. (LEMM). Using manual and digital Technologies, we seek to espose the mathematics presente in solving the symmetry problem in nature, working with a natural elemento: flowers. Within the available conditions and tools the Geogebra software was a potentially significant tool for the Mathematicl Modeling process, as it facilited the obtaining of results and demonstration of symmetry or non-symmetry of the seceted flowers.